Will regulatory issues continue to be a major barrier to access to bedaquiline and delamanid?. Issue 3 (22nd March 2018) - Masini, Tiziana; Hauser, Janika; Kuwana, Rutendo; Nhat Linh, Nguyen; Jaramillo, Ernesto
In 2016, 600 000 people are estimated to have been eligible for multidrug-resistant (MDR) tuberculosis (TB) treatment [1]. Bedaquiline and delamanid are the first two new anti-TB compounds to have become available in over four decades and were approved by stringent regulatory authorities a in 2012 and 2014 respectively [3, 4]. The global introduction of bedaquiline and delamanid has not kept pace with the dire need for these potentially life-saving drugs [5, 6]. Despite a number of initiatives intending to enable access [7–14], the number of patients who have received these drugs remains unacceptably low. Very few MDR-TB high burden countries have fully integrated either bedaquiline or delamanid into their National TB Programmes (NTPs) [1, 15, 16]. While costs and concerns over adverse events may have contributed to hesitation in the adoption of bedaquiline and delamanid, a frequently cited cause for delay is the lack of national regulatory approval. b Although subject to an often long process, regulatory approval is meant to serve a public good and remains essential for sustainable import, programmatic use and therefore patient access to the drugs [17]. Despite being referenced in past reports [18], the challenges faced by drug manufacturers and National Medicines Regulatory Authorities (NMRAs) when registering the drugs have not yet been investigated more completely. National regulatory approval of life-saving TB drugs to be streamlined via improved communication and information sharing http://ow.ly/8Ti130i8mID